Senam Aerobik Low Impact Hafalan Dan Senam Aerobik Low Impact Video Dapat Meningkatkan Konsentrasi Pada Remaja - Arfanda, Poppy Elisano; Hasmyati, Hasmyati; Syahruddin, Syahruddin; Aprilo, Ians; Arimbi, Arimbi; Mappaompo, M. Adam; Latuheru, Ricardo Valentino; Puspodari, Puspodari; Putera, Shidqi Hamdi Pratama (Journal of Sport Science and Education, 2023)
This study analyzes the differences between the concentration levels of the rote low-impact aerobics dance group and the video low-impact aerobics dance group. The subjects in this study were 36 adolescents aged 18-20 years who voluntarily participated. Subjects were divided ordinal pairing into two groups, namely 18 people in the rote low-impact aerobics dance group and 18 people in the video low-impact aerobics dance group. The duration of the exercise is 30 minutes sessions with an intensity of 50-70% HRmax, and the frequency of exercise is 3 times/week for 6 weeks. Concentration levels were evaluated pretest and posttest the intervention using the Grid Concentration Test. The data analysis used the Independent Sample Test with a significant level (p ≤ 0.05). The results showed that there was an increase in the average concentration between the pretest and posttest in the rote low-impact aerobics dance group (scores 6.89 ± 2.45 and 9.56 ± 2.64, p = 0.000), and the video low-impact aerobics dance group (scores 7.39 ± 2.38 and 9.11 ± 2.45, p = 0.000). Based on the pretest and posttest data it was concluded that there was an increase in the level of concentration in both groups, but there was no difference between the rote low-impact aerobics dance and video low-impact aerobics dance on concentration.